2022
DOI: 10.3390/electronics11152384
|View full text |Cite
|
Sign up to set email alerts
|

CMT-SCTP and MPTCP Multipath Transport Protocols: A Comprehensive Review

Abstract: A huge amount of generated data is regularly exploding into the network by the users through smartphones, laptops, tablets, self-configured Internet-of-things (IoT) devices, and machine-to-machine (M2M) communication. In such a situation, satisfying critical quality-of-service (QoS) requirements (e.g., throughput, latency, bandwidth, and reliability) is a large challenge as a vast amount of data travels into the network. Nowadays, strict QoS requirements must be satisfied efficiently in many networked multimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 233 publications
0
6
0
Order By: Relevance
“…As more and more dataintensive video applications, such as ultra-high-definition video, AR/VR, and even high-resolution 3D holographic images enter mobile devices in the future, multipath technology has gradually become the focus of attention. However, the development of some multipath transmission protocols is limited due to their incompatibility with Network Address Translation (NAT) devices, such as the Concurrent Multipath Transfer for Stream Control Transmission Protocol (CMT-SCTP) based on SCTP extensions [10]. In addition, the deployment resistance of MultiPath TCP (MPTCP) based on TCP extension is very large, and most research is in path management and data scheduling [11].…”
Section: Related Workmentioning
confidence: 99%
“…As more and more dataintensive video applications, such as ultra-high-definition video, AR/VR, and even high-resolution 3D holographic images enter mobile devices in the future, multipath technology has gradually become the focus of attention. However, the development of some multipath transmission protocols is limited due to their incompatibility with Network Address Translation (NAT) devices, such as the Concurrent Multipath Transfer for Stream Control Transmission Protocol (CMT-SCTP) based on SCTP extensions [10]. In addition, the deployment resistance of MultiPath TCP (MPTCP) based on TCP extension is very large, and most research is in path management and data scheduling [11].…”
Section: Related Workmentioning
confidence: 99%
“…In addition to this protocol it also keeps redundant paths for backup. A related study [16] also showed that different network configurations also agree that the performance of SCTP is better through several parameters. The study in the area of wireless sensor networks is carried by authors in [17].…”
Section: Literature Reviewmentioning
confidence: 81%
“…Model performance was quantified by evaluating precision, recall, F1-score, and accuracy. The implementation was performed with the help of the Scikit-Learn library [63][64][65][66]. 2 shows the comparison of results of the multi-tier and single-tier models.…”
Section: Implementation Of Multi-tier Modelmentioning
confidence: 99%